The Model of Rational Education and Training Based on Islamic Teachings In Line With the Productivity of Human Resources in Prison Using the Meta-Synthetic Method - Mikael Jamalpour; Karim Esgandari; Shadi Orafaye Jamshidi (مدیریت بهره وری, 2025)
Abstract The aim of the current research was designing a model of rational education based on Islamic teachings to enhance human resources productivity. To achieve this goal, a hybrid method was used. Initially, various texts, sources and researches related to the research subject were studied, and the themes related to the model of rational education and training in line with the efficiency of human resources based on Islamic teachings were identified. Next, the identified codes were compiled into an expert questionnaire, and the experts provided the final model by sharing their opinions and incorporating them into the model. Then, the presented model was validated. The final model of rational education and training based on Islamic teachings in Tabriz prison aimed at enhancing human resources productivity includes 5 dimensions, 16 components and 98 indicators. The first dimension, education and training of resourcefulness, includes the components of slamic intellectual education, Islamic thinking education, and Islamic education;  the second dimension learning based on Islamic teachings, encompasses Islamic role model education, and Islamic experience education; the third dimension, benefit from dynamic training, includes educational methods, and new justice-oriented education; the fourth dimension, planning of educational processes, focuses on software planning of education, and hardware planning of education; and the fifth dimension, education and training of human religious components, includes the components of Social education, moral education, physical education, spiritual and religious education, education of good human qualities, and Islamic self-education.      Key Words: Islamic teachings, human resources productivity, rational education, rational training, Tabriz prison   1.Introduction Considering the importance of rational education and training based on Islamic teachings in the prison organization as well as the educational measures of the country, there is no coherent and integrated model that addresses the indicators of rational education and training grounded in Islamic teachings. In order to improve the effectiveness of prison rehabilitation and education programs, rational education based on Islamic teachings can be effective. The question of the present research is as follows: What is the model of rational education and training grounded in Islamic teachings in line with the productivity of human resources in prison? 2.Literature Review According to a review of the empirical foundations of the research, it is evident that the issue of rational education and training based on Islamic teachings has been examined in various researches from different aspects; however, there is currently no coherent and integrated model specifically designed for the prison organization that addresses the educational and training measures  of the country while taking into account the political, cultural, and prevailing ruling values within the prison context.Therefore, the present research, is an attempt to present a model of rational education and training grounded in Islamic teachings in order to enhance the productivity of human resources. 3.Methodology The current research employs a mixed-methods approach, encompassing both qualitative and quantitative stages. In the qualitative stage of the study, using meta-synthetic method, the researcher tries to extract categories (dimensions), concepts (components) and codes (indices) related to rational education and training based on Islamic teachings through a systematic literature review and to propose the research model. In the quantitative stage, the preliminary model of the research is surveyed by experts using the survey method while taking into account the conditions of Iran's state organizations in order to adapt and localize the model. 4.Result The results of the data analysis revealed that the current research model consists of 5 dimensions, 16 components and 98 indicators that can show the model of rational education in Tabriz prisons organization. Based on the results obtained from the meta-combination analysis and expert survey, it can be said that all five dimensions including: 1. Education and training of resourcefulness, 2. Learning based on Islamic teachings, 3. Benefiting from dynamic education, 4. Planning educational processes and 5. Education and training of human religious components in education and Intellectual education based on Islamic teachings in Tabriz prison play a significant role in Iran's state organizations. 5.Conclusion Considering the importance of the research problem and also a review of the literature and background of the research, the necessity of designing a model of rational education based on Islamic teachings was felt in Tabriz prison. In the initial steps of the research and according to his initial studies in the field of the topic, the researcher came to the point that past researchers do not have a significant consensus regarding the definition, types and dimensions of rational education grounded in Islamic teachings. Investigations showed that, from the point of view of some experts, the main reason for not achieving such a consensus was the lack of proper attention to the multifaceted nature of education. Rational education is a relatively new and broad concept in the field of social sciences and psychology. Therefore, it seemed necessary to adopt combined methods that could obtain the results of past research in a systematic way and help researchers to find regular patterns. Since the relatively new meta-synthetic approach has not yet been widely used in this field, it could be a valuable tool to facilitate the theory building process through systematic combination. In order to adapt and localize the extracted model from the meta-synthetic method, the researcher put the extracted categories (dimensions), concepts (components) and codes (indices) through a questionnaire (questionnaire number one) at the disposal of academic experts and managers of the prison organization who were qualified as research experts to evaluate the content validity of the model. After confirming the initial research model by indicators related to relative coefficient of content validity (CVR), in the next step, the researcher set questions to measure the research codes. One question was set for each code. Questionnaire number two was given to the experts in order to relate regulatory questions with extracted codes. After confirming the questions of the questionnaire by the indicators related to the content validity index (CVI), the final model of rational education based on Islamic teachings was also approved by the expert community.   Conflict of interest: none